Enhanced strength–ductility synergy in nanostructured Cu and Cu–Al alloys processed by high-pressure torsion and subsequent annealing - An, X.H.; Wu, S.D.; Zhang, Z.F.; Figueiredo, R.B.; Gao, N.; Langdon, T.G. (Scripta materialia, 2012)
Nanostructured Cu and Cu–Al alloys processed by high-pressure torsion were isochronally annealed to investigate the effects of the stacking fault energy (SFE) on strength and ductility. All metals exhibit a similar general trend that the strength decreases and the ductility improves with increasing annealing temperatures, and a notable enhancement of ductility was achieved only when the volume fraction of recrystallized grains exceeded ∼80%. The strength–ductility synergy improves significantly with decreasing SFE.